2018
DOI: 10.1371/journal.pone.0209389
|View full text |Cite
|
Sign up to set email alerts
|

A high-throughput, whole cell assay to identify compounds active against carbapenem-resistant Klebsiella pneumoniae

Abstract: Enteric Gram-negative rods (GNR), which are frequent causes of community-acquired and nosocomial infections, are increasingly resistant to the antibiotics in our current armamentarium. One solution to this medical dilemma is the development of novel classes of antimicrobial compounds. Here we report the development of a robust, whole cell-based, high-throughput metabolic assay that detects compounds with activity against carbapenem-resistant Klebsiella pneumoniae. We have used this assay to screen approximatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…The UV visualization results showed a characteristic band of light absorption for zinc oxide nanoparticles in the range of 360–380 nm. This is similar to the results reported by Zare et al, who showed that the absorption peak for synthesized ZnO nanoparticles was in the range of 360–376 nm [ 19 ]. Other similar results were reported by Padalia et al and Safawo et al, who found that ZnO-NPs synthesized using A. hydrophila and O. europea extract showed an absorption peak 374 nm.…”
Section: Discussionsupporting
confidence: 91%
“…The UV visualization results showed a characteristic band of light absorption for zinc oxide nanoparticles in the range of 360–380 nm. This is similar to the results reported by Zare et al, who showed that the absorption peak for synthesized ZnO nanoparticles was in the range of 360–376 nm [ 19 ]. Other similar results were reported by Padalia et al and Safawo et al, who found that ZnO-NPs synthesized using A. hydrophila and O. europea extract showed an absorption peak 374 nm.…”
Section: Discussionsupporting
confidence: 91%
“…In Saudi Arabia, the high incidence of KPC may be due to the large number of pilgrims, visitors, and migrant workers from endemic countries such as Turkey, India, and Pakistan every year ( Liao et al., 2018 ). Surveys such as that conducted by Faiz and Khan have shown that the incidence of KPC among Makkah hospitals is about 48.4% from other carbapenem-producing organisms ( Aftab Faiz, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic manipulation has also been utilized to help finding molecular targets of antibacterial agents, such as sensitive-resistant pair screening (philipimycin), target upregulation or overproduction and gain of the control rescue assay (novobiocin), reduced expression of target or hypersensitive screening (cerulenin), etc. Traditional CT-HTS and MT-HTS assays using either natural products or synthetic molecule libraries have generally been more successful in identifying anti-gram-positive antibacterial agents than anti-gram-negative antibacterial agents with some exceptions [ 49 ]. However, HTS using multicopy suppressor containing the genomic library of E. coli demonstrated successful identification of antibiotic targets in addition to demonstrating the roles of multidrug efflux pump in reducing the success of antibiotics, a major problem for gram-negative bacteria [ 50 ], which in general has a hit rate of 1–2 reduced orders of magnitude more than gram-positive, S. aureus [ 33 ].…”
Section: Approaches and Strategies For Antibacterial High-throughput ...mentioning
confidence: 99%